The ecological-health risks of potentially toxic metals in the surface sediments and leaves of salt-secreting Avicennia officinalis as potential phytoremediators: a field-based biomonitoring study from Klang mangrove area - Yap, Chee Kong; Al-Mutairi, Khalid Awadh (Multidisciplinary Digital Publishing Institute, 2022)
This study aimed to evaluate the ecological-health risks of potentially toxic metals in the surface sediments on the Klang mangrove ecosystem and assessed the phytoremediation potential of Avicennia officinalis collected from the area. The results showed that the concentrations (mg/kg dry weight) of Cu, Ni, Pb and Zn in the surface sediments ranged between 5.30–63.8, 14.2–32.7, 30.3–62.3, and 46.4–269, respectively. The ecological risk values of the surface sediments indicated that Ni, Pb and Zn were all classified as ‘low potential ecological risk’, while the Cu ecological risk ranged between ‘low potential ecological risk’ and ‘considerable potential ecological risk’. For the health risks on the sediments, all of the values of hazard index for Cu, Ni, Pb and Zn, based on a combination of three pathways, indicated < 1.00, showing that the four metals are non-carcinogenic. Based on the bioconcentration factor values, it can be concluded that the lamina has better potential as a phytoremediator of essential Cu, Zn and Fe. In contrast, midrib plus petiole has better potential as a phytoremediator of non-essential Pb and Ni. To mitigate the threats to the Klang mangrove ecosystem, the information offered in the present study can be employed in the monitoring and provision of the ecological-health risks of potentially toxic metals in the Klang mangrove ecosystem. Hence, the present findings can be employed for developing a water-energy-food framework for managing the Klang mangrove ecosystem.